Volatile constituents of Cunila polyantha (Lamiaceae) fr.om .costa Rica. A rich source of menthone - Cicció, José F. (Universidad de Costa Rica, 1999)
The constituents of the volatile oil of Cunila polyantha from Dota, Costa Rica, were investigated using coupled gas chromatography-mass spectrometry (GC-MS) analyses. Menthone (63%), pulegone (14%), P-caryophyllene (4.5%) and 3-octanyl acetate (3%) were found to be the major constituents of the volatile oil.